2020
DOI: 10.1002/smll.202000655
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Engineering of a Scavenger‐Free Nitric Oxide‐Generating/Delivering System to Enhance Radiation Therapy

Abstract: Nitric oxide (NO) is a potent tumor‐cell radiosensitizer but it can be readily scavenged by hemoglobin (Hb) in vivo. A biomimetic incubator that can generate and deliver NO in a scavenger (Hb)‐free environment to enhance its radiosensitizing effect to maximize its efficacy in radiotherapy is proposed. This NO incubator comprises a poly(lactic‐co‐glycolic acid) (PLGA) hollow microsphere (HM) that contains an NO donor (NONOate) and a surfactant molecule (sodium caprate, SC) in its aqueous core. In acidic tumorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…S-nitrosoglutathione (GSNO) is a prodrug that can generate nitric oxide (NO) under the presence of glutathione (GSH) [ 99 ]. Many studies have revealed that NO has the potential to overcome multidrug resistance (MDR) with low side effects [ 100 ]. However, GSNO is unstable and its stability can be easily affected by ambient temperature, pH and other factors.…”
Section: Micellementioning
confidence: 99%
“…S-nitrosoglutathione (GSNO) is a prodrug that can generate nitric oxide (NO) under the presence of glutathione (GSH) [ 99 ]. Many studies have revealed that NO has the potential to overcome multidrug resistance (MDR) with low side effects [ 100 ]. However, GSNO is unstable and its stability can be easily affected by ambient temperature, pH and other factors.…”
Section: Micellementioning
confidence: 99%
“…Layers of SC surfactant then trap and stabilize NO molecules and they are together released from the PLGA shell due to the increased pressure. Outside the PLGA shell, NO molecules slowly diffuse from the encapsulation of SC, providing elongated radiosensitizing effects which inhibit tumor growth [58]. In another study, gold core-mesoporous silica shell rod-like nanoparticles (AuMSSs) and salicylic acid (SA) were loaded inside the microspheres made of PLGA, poly (vinyl alcohol) (PVA), and D-α-tocopherol polyethylene glycol succinate (TPGS).…”
Section: Anti-cancer Drug Deliverymentioning
confidence: 99%
“…On the other hand, nitric oxide (NO) can effectively inhibit tumor cell respiration and facilitate tumor vessel normalization, which thereby increase the perfusion of blood, alleviate tumor hypoxia, polarize M2 macrophages to the M1 phenotype, and reduce the number of myeloid-derived suppressor cells (MDSCs) ( Ramesh et al, 2020 ). Furthermore, many studies have demonstrated that NO could react with the ROS produced by PDT or SDT, which could generate more powerful oxidant reactive nitrogen species (RNS) to reverse the immunosuppressive TME and achieve more effective antitumor effect ( An et al, 2020 ; Lin et al, 2020 ; Xiang et al, 2021 ). Therefore, Ji et al (2021) constructed a mitochondria-targeting, US-responsive nanoparticle (named PIH-NO), which could deliver O 2 and NO at the same time to amplify SDT and increase immune response.…”
Section: Mitochondria Targeting With the Aid Of Multifunctional Nanosystemsmentioning
confidence: 99%